The queen of Versailles [videorecording (DVD)] - Greenfield, Lauren; Nebab, Virginia (Magnolia Home Entertainment, 2012)
The Queen of Versailles is a character-driven documentary about a billionaire family and their financial challenges in the wake of the economic crisis. The film follows two unique characters, whose rags-to-riches-to-rags success stories reveal the innate virtues and flaws of the American Dream.